The process of firm establishment in less developed and loosely structured markets : a case study of two Swedish firms in Kenya / Desalegn Abraha and Syeda-Masooda Mukhtar - Abraha, Desalegn; Mukhtar, Syeda-Masooda (Faculty of Business and Management ; UiTM Press, 2002)
While much attention has been paid to the study of estabhshment processes of MNCs within developed countries, researchers have largely ignored the developing country perspective. As a result, understanding of such processes within the developing country context remains relatively limited. Against this background, this paper endeavors to explore the salient features of the estabhshment processes of two Swedish firms, SKF and Alfa-Laval, in Kenya using the network approach. In view of its findings, the paper concludes with specific policy measures for both MNCs and governments of developing countries.